Starch Characterisation ofAraucaria angustifolia andAraucaria araucana Seeds - Conforti, Paula Andrea (2007)
Araucaria angustifolia and Araucaria araucana are conifers that cover different areas of South America. Their seeds have been consumed from prehistoric times until today in Brazil, Argentina and Chile. In this work, the starch of Araucaria angustifolia and Araucaria araucana seeds were analysed by light and environmental scanning microscopy, X-ray diffraction, and differential scanning calorimetry. The starch granules of A. angustifolia and A. araucana were round or slightly oval, with a central hilum. Both starches gave X-ray diffraction patterns compatible with the A-type, with strong peaks at 15°, 17°, and 23°. The gelatinization temperature of A. angustifolia starch (68.5 °C) was higher than that of A. araucana (66.6 °C), probably due to the higher amylose content of the former (22.4 % and 17.3 %, respectively). The thermograms of A. araucana starch presented a minor peak at about 71 °C, which was attributed to the fact that the starch granules population of A. araucana was heterogeneous, with large and small granules, whereas A. angustifolia starch contained mainly large granules.